Romantic reclusion in the works of Cowper and Wordsworth - Clucas, T (2014)
The end of the eighteenth century witnessed an imaginative mass migration as authors wrote about withdrawing from society. This thesis traces the origins of 'Romantic reclusion' in the works of Cowper and Wordsworth, particularly Cowper's poem The Task and Wordsworth's unfinished masterwork The Recluse, which epitomise the tradition. Romantic reclusion differs from 'solitude' and 'retirement' in that its motives were social. Cowper and Wordsworth wrote about withdrawing in order to criticise the increasing commercialism and competition they saw in British society. Both poets imagined seceding into a community of individuals who would care for a shared set of values, envisaging this as a form of non-violent political protest leading to reform. The thesis builds on recent studies of Romantic community, and develops Raymond Williams's cultural criticism, to refute the New Historicist position that Romantic writing elides history. It proceeds by historicising Cowper's and Wordsworth's concepts of reclusion, tracing echoes of their extensive reading about this subject in what they wrote. Romantic reclusion emerges as an artistic attempt to defend the individual against the dehumanising effects of contemporary society. Its aims can be grouped under four interrelated headings-'creative', 'medical', 'political', and 'natural'-which form the basis of the chapter divisions. Chapter One argues that Cowper and Wordsworth both presented Milton as a precedent for their poetic reclusion. They withdrew from literary society and cut themselves off from the diction of eighteenth-century poetry, because they believed that it turned words into luxury items which could only be purchased by the imaginations of a few. Cowper's translations of Madame Guyon and Wordsworth's modernisations of Chaucer both attempted to develop a plain style which would unite a wider, non-hierarchical community of readers. Chapter Two explores the origins of Cowper's reclusion in his spiritual crisis of 1763-5. Beginning with a study of medical books owned by Cowper's doctor, Nathaniel Cotton, it argues that Cotton regarded Cowper's illness as a product of eighteenth-century models of sociability. Both Cowper and Wordsworth employed Robert Burton's concept of 'Honest Melancholy', or sorrow for the state of one's country, to critique social competition and call for new models of community. Chapter Three examines Cowper's and Wordsworth's presentations of reclusion as the best response to the violence of the American and French Revolutions. Drawing on the works of Classical and modern historians, both poets argued that political revolutions would only succeed once individuals learned to renounce self-interest and govern their selfish passions. The 'retired man' becomes the unexpected political hero of The Task, which in turn forms the basis for Wordsworth's conception of The Recluse. Finally, Chapter Four explores Cowper's and Wordsworth's interests in natural theology, arguing that both poets built on the works of writers including Calvin, David Hartley, and Joseph Butler to explain the psychological mechanism by which reclusion in nature could help to reform the mind, eliminating the selfish passions and teaching individuals to live in an active, mutually responsible community.